Public spaces times of crisis and change - Lopes, Joa<U+0303>o Teixeira; Hutchison, Ray. (Bingley, U.K. : Emerald, 2016)
This volume is about the plurality and complexity of modern urban public spaces. The authors move far beyond the nostalgia of traditional streets, squares and gardens to mobilize contemporary sociological knowledge based on the mediated relations between spatial morphology and everyday life in cities across several continents. Contributions analyse diverse social realities and social interventions within the context of urban public spaces, linking to the broader discussion of urban public policies in European cities and beyond. Sometimes these interventions lead to exclusionary processes; other times they are the object of conflicts and resistances. When we speak about the (re)constructions, the uses and counter-uses of urban public spaces, we are always in the core of the political (city: polis) domain as those places are not fixed and do not have unique representations or immutable configurations they are networks of relationships and social practices with antagonistic views and flexible uses.
Urban space and public places / Ray Hutchison, Joa<U+0303>o Teixera Lopes-- Public spaces: interactions, appropriations and conflicts / Luciana Teixeira de Andrade, Lui<U+0301>s Vicente Baptista -- Is the city unnecessary? New life spaces of young city inhabitants / Marta Smagacz-Poziemska -- Sidewalk encounters: card playing and neighborhood use in a Lisbon suburb / Joa<U+0303>o Pedro Nunes -- Sala Borsa: plural presences and innovative public spaces / Luca Daconto, Gabriele Manella -- Transformation of public space in Zagreb since 2000 / Jelena Zlatar Gamberoz<U+030c>ic, Andelina Svircic Gotovac -- Artists' studios in urban areas: a comparative study between Paris and London / Dominique Billier -- Typifying the thematic cities: study of the events organized in public spaces in the cities of Oporto, Vila Nova de Gaia and Barcelona / Fernando Manuel Rocha da Cruz -- Shaping a territory. Case study: the Moorish Quarter in Lisbon (Mouraria) / Madalena Corte-Real -- The spatial analysis of Gezi Movement in Turkey / C<U+0327>agri Eryilmaz -- Contested cityscapes: politics of vertical construction in Paris and Vienna / Andrea Glauser -- Heritage, place and neighbourhood: itineraries as public space contention in ring-road districts of Madrid / Pedro Limo<U+0301>n Lo<U+0301>pez, Sergio Claudio Gonza<U+0301>lez Garci<U+0301>a -- Researching social stratification in large urban zones today / Juan Jose<U+0301> Villalo<U+0301>n-Oga<U+0301>yar -- Rethinking public spaces in waterfront areas: notes from Lisbon / Patri<U+0301>cia Pererira -- The earthquake and the shanty. Post-disaster social order in a Sicilian town (1908-2013) / Domenica Farinella, Pietro Saitta -- From exclusion to participation: social mediation in public housing / Micol Bronzini, Carla Moretti -- Sociological intervention as a reaction to the crisis of the city: public consultation in Warsaw / Przemyslaw Sadura, Dorota Olko.
Includes bibliographical references.
Print version record
Keywords: Social Science -- Sociology -- Urban; Urban communities; Sociology; Public spaces